Pengaruh Citra Dan Keramahan Karyawan Terhadap Kenyamanan Tamu Pada Grand Sahada Hotel Aek Batu - Ismayana, Ismayana; Pristiyon, Pristiyon; Zufrie, Zufrie (LPPM Universitas Labuhanbatu, 2021)
This study aims to examine the effect of image and friendliness of employees on guest comfort at Grand Sahada Hotel AEK Batu, South Labuhanbatu Regency. Data collection was carried out by distributing questionnaires and distributed to 60 research samples, namely grand sahada hotel guests. Data analysis in this study using the help of SPSS version 20. Data testing techniques conducted in this study include validity and reliability test, classical assumption test, multiple linear regression analysis, and partial and simultaneous testing. The analysis showed that the image of a positive effect on the comfort of guests it is seen from the value of t count > t table (2.697>2.002), and the hospitality of employees a positive effect on the comfort of guests it is seen from the value of t count > t table (4.318>2.002), image, atmosphere, quality and friendliness of employees a positive effect on the comfort of guests it is seen from the value of F count > F table (13.558>2.77).